SOCIALIZATION OF THE TAMYIZ METHOD FOR ISLAMIC RELIGIOUS EDUCATION TEACHERS - Akil .; Safuri Musa; Abdul Kosim; Rohmat Tulloh; Ayu Fitria Lestari (Institut Pendidikan Tapanuli Selatan, 2022)
Implementation of the Tamyid Method as Accelerated Learning in the translation of the Qur'an as a focus of Research and Community Service (PkM) is a form of actualization or a form of community service work in disseminating and providing assistance to Islamic Religious Education (PAI) teachers so that they are qualified and professional in carrying out their duties. The task of fostering and developing competence for students, especially Middle School Students/Students/Pondok Pesantren Bayt Tamyiz, Tukdana District, Indramayu Regency. These activities are designed to realize students who can develop their potential optimally. To realize this, Islamic Religious Education (PAI) teachers must understand and be able to implement it in the learning process. The role of PAI teachers must also be able to socialize in the learning process through the Tamyiz Method as Accelerated Learning in the translation of the Qur'an, which is a necessity that should be considered because it has a role in efforts to improve student learning outcomes. The purpose of this community service is to describe the role of PAI teachers in the form of assistance in improving student learning outcomes. PAI teachers improve student learning outcomes in their collective contribution through the Islamic Religious Education Subject Teacher Consultation (MGMP PAI) and as coaches, which are specifically implemented to assist schools/institutions/communities. Socialization of the Tamyiz Method for Islamic Religious Education teachers will determine success in improving the quality of student learning outcomes because the Tamyiz method is straightforward and fast in learning, memorizing, understanding, appreciating, and translating the Qur'an.